Unique Findings and Novel Treatment Strategy of a Giant Coronary Artery Aneurysm Associated with a Significant Pericardial Effusion - Osayi Lawani; Rick Ganim (Case Reports in Cardiology)
Giant coronary artery aneurysms are a rare, asymptomatic occurrence. Presently, there is a lack of substantial research performed in the U.S., likely due to its low prevalence. As we are increasingly becoming a global community, strengthening data for seemingly rare disease processes such as this need to be addressed, particularly when they can progress to involve complications such as pericardial effusion caused by aneurysmal rupture or infection. A popular treatment option for these aneurysms is polytetrafluoroethylene-covered stents; they have been favorable with obtaining a high percentage of procedural success rates in aneurysms not associated with myocardial infarctions. In this paper, we present a case of a giant coronary artery aneurysm located in the left circumflex coronary artery that was complicated by a pericardial effusion. We will also present its unusual repair using a long drug-eluting stent as a scaffold to overlap covered coronary stents used to help exclude the aneurysm.